LINKING ONLINE AND OFFLINE SOCIAL LIFE THROUGH DIGITAL GAMING - Eklund, Lina (AoIR Selected Papers of Internet Research, 2015)
The aim is to shed light on the connections between online and offline life by analysing digital gaming using a relational sociological perspective. Relational sociology focuses on understanding the dynamic ebb and flow of social relationships between actors, and how these shape social world(s). Emirbayer (1997) argues that attention to relations offers a perspective where researchers can see how the world unfolds as processes in an increasingly moving world. By exploring connections between people this study shows how intimately linked online and offline life is in the everyday lived experiences of digital gamers. At the same time a clear paradox is experienced as users express an ideal of the global Internet, reducing boundaries between people. Yet this ideal is not realised in peoples’ practises. The study contributes with both in-depth understanding of how online and offline life is connected in practice but also suggests how to theoretically, in a relational perspective, understand online life’s intimate connection to the offline.